2011
DOI: 10.1889/1.3621102
|View full text |Cite
|
Sign up to set email alerts
|

P‐76: Combined Nanostructured Layers for Display Applications

Abstract: One-step cost effective process of fabrication of a full inorganic nanostructured transparent conductive electrode and LC alignment layer has been developed. More specifically, the subject comprises a self-organized nanomesh of a valve metal, concomitant porous oxide layer with various functionality and electrochemical method of their fabrication. The nanomesh film is electrically conductive, optically transparent and flexible. It can be fabricated on a variety of substrates, including flexible and rigid subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The electrochemical anodization technique of inorganic films on a glass substrate, which provide simultaneously a high optical transparency and good alignment properties for LC molecules on the substrate surface, is one of the promising solutions for the design and production of next generation of displays . At the same time, different reaction possibilities for the functional groups and the cyclic fragments of the corresponding substituted cyclohexenones, isoxazolines, and similar to them intermediates allow transformations to be achieved selectively and give a chance of preparing anisotropic compounds and materials with novel combinations of the structural fragments of molecules .…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical anodization technique of inorganic films on a glass substrate, which provide simultaneously a high optical transparency and good alignment properties for LC molecules on the substrate surface, is one of the promising solutions for the design and production of next generation of displays . At the same time, different reaction possibilities for the functional groups and the cyclic fragments of the corresponding substituted cyclohexenones, isoxazolines, and similar to them intermediates allow transformations to be achieved selectively and give a chance of preparing anisotropic compounds and materials with novel combinations of the structural fragments of molecules .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the alkanoylcyclohex-2-enones, alkanoylcyclohexanones, and similar to them diketones are promising intermediates for the preparation of various liquid crystalline compounds [1][2][3]. Additionally, we presented novel approach to fabrication of fast switching VA LCDs [4,5]. The electrochemical anodization technique of aluminum films on a glass substrate, which provide simultaneously a high optical transparency, a low electrical resistivity of the work substrate, and good alignment properties for LC molecules on the substrate surface, is one of the promising solutions for the design and production of next generations of displays.…”
Section: Introductionmentioning
confidence: 99%
“…The novel low‐temperature nonlithography method of transparent conductive electrodes fabrication will be discussed. The electrochemical anodization/etching of aluminum film is a key component for this method . It allows fabricating a self ordering aluminum transparent electrode with 70–80% average transmission in the visible range and 10–20 Ω/A sheet resistance .…”
Section: Introductionmentioning
confidence: 99%